Effectiveness of Birth Planning in Preventing Postpartum Depression: Evidence from Independent Midwifery Practices in West Java Indonesia - Desi Trisiani; Armiyanti Ahmad Rizwanda; Noucie Septriliyana; Siti Nur Endah Hendayani; Nurmiaty Nurmiaty (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Postpartum depression is a common mental health disorder among women after childbirth, with high prevalence in developing countries, including Indonesia. Inadequate birth preparation may increase maternal stress and emotional disturbances during the postpartum period. This study aimed to examine the effect of a birth plan on the prevention of postpartum depression in independent midwifery practices in the Derwati Health Center area, Bandung City. Methods: A quasi-experimental study with a post-test only control group design was conducted on 30 third-trimester pregnant women, divided into an experimental group (with a birth plan) and a control group (without a birth plan). Postpartum depression was measured using the Edinburgh Postnatal Depression Scale (EPDS). Data were analyzed using the Mann– Whitney test. Results: In the experimental group, 1 respondent (6.7%) experienced postpartum depression, compared with 2 respondents (13.3%) in the control group. The Mann–Whitney test indicated a statistically significant difference between groups (p = 0.019). However, the small sample size limits the generalizability of these findings. Conclusion: Birth planning may contribute to reducing the risk of postpartum depression; however, larger and more rigorous studies are required to confirm this finding.